Cues for movement in monkeys (Macaca mulatta) with lesions in premotor cortex. - Passingham, R (1986)
It has been shown previously that after removal of premotor cortex, monkeys are poor at selecting movements on the basis of a visual contextual cue. In those experiments, the monkeys had to pull or turn a handle depending on the color of a cue presented in the foreground or background. In the present experiments, it is shown that animals with lesions that include premotor cortex can select movements correctly if the cue is given by information about the handle itself. In the first experiment, the cue was provided by the direction in which the monkey had last moved the handle; the monkeys had been required to squeeze a handle if they had been forced to squeeze it 5 s earlier, and they were required to turn it if they had been forced to turn it. In the second experiment, the cue was provided by the identity of the handle itself: When presented with a blue handle, they had to pull the handle; when presented with a yellow handle, they had to turn it. It is argued that the animals are impaired only when the task is a true conditional task.